Management of Thoracolumbar Fractures - Sanjay Meena; Pankaj Sharma; Buddhadev Chowdhury (Indian Journal of Neurosurgery)
Abstract Thoracolumbar region is the most commonly affected region of spine in trauma, but still no consensus exists on various aspects of its management. The management of thoracolumbar fractures has evolved considerably with time, but there are certain areas where there is still no consensus. Only few level I evidence are available to make any recommendation. This article reviews the current literature on evaluation, treatment, timing of surgery, choice of approach, and length of fusion.